2005
DOI: 10.1080/08923970500241071
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mycotoxins on Some Activities of Isolated Human Neutrophils

Abstract: Activities of mycotoxins--citrinin, ochratoxin B, rubratoxin B, and zearalenol beta--that affected superoxide anion (O2-) production were studied on human neutrophils with regard to hypochlorous acid (HOCl) generation, nitric oxide (NO) formation, and chemotaxis of isolated cells. At the doses of 10(-8), 10(-6), 10(-4), or 10(-2) mg/mL, in stimulated cells the mycotoxins inhibited HOCl production proportionally to that of O2- because HOCl production is directly dependent on O2- generation. But unlike the other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 23 publications
1
5
0
1
Order By: Relevance
“…Another gene that was downregulated by ochratoxin A, PLCG2, has been linked with leukocyte migration before: a patient carrying a missense mutation in PLCG2 had impaired leukocyte chemotaxis (Zhou et al, 2012). Our results are in concordance with those of Richetti et al, who demonstrated that several mycotoxins, including ochratoxin B, are potent inhibitors of chemotactic peptide-induced chemotaxis of human primary neutrophils (Richetti et al, 2005).…”
Section: In Vitro Immunotoxicity Testssupporting
confidence: 91%
“…Another gene that was downregulated by ochratoxin A, PLCG2, has been linked with leukocyte migration before: a patient carrying a missense mutation in PLCG2 had impaired leukocyte chemotaxis (Zhou et al, 2012). Our results are in concordance with those of Richetti et al, who demonstrated that several mycotoxins, including ochratoxin B, are potent inhibitors of chemotactic peptide-induced chemotaxis of human primary neutrophils (Richetti et al, 2005).…”
Section: In Vitro Immunotoxicity Testssupporting
confidence: 91%
“…Using formyl-Met-Leu-Phe as chemoattractant, an inhibitory effect of ochratoxin B and zearalenone was observed at low concentration (3 nM to 30 M) on the chemotaxis of human neutrophils [16]. A previous study showed that the random migration of porcine neutrophils was not affected by low concentrations (0.1-10 M) of DON [17] suggesting that DON interfered with the signal between chemoattractant and the PMNs but did not affect the capacity of PMNs to move in the surroundings.…”
Section: Discussionmentioning
confidence: 94%
“…Immune cells are a primary target for DON, and depending on the dose and frequency of exposure, DON can be either immunosuppressive at high concentration or immunostimulatory at low concentration. The immunomodulatory effects of DON have been described on a macrophage cell line , natural killer cells , lymphocytes , and dendritic cells but very few studies have investigated the effect of DON on polymorphonuclear cells (PMNs) . PMNs constitute the first line of defense against intruding microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…Notably however, the phagocytic ability of neutrophils was significantly reduced after 17 days (Müller et al, 1995), suggesting that cellular function was impaired. Application of ochratoxin A to human neutrophils in vitro stimulated a dose-dependent activation of the oxidative burst response from 2 h, an increase in the level of intracellular calcium from 4 h and adenosine triphosphate depletion and necrosis from 8 and 20 h, respectively (Kupski et al, 2016), while 25 µM treatment impaired chemotactic and NO responses (Richetti et al, 2005).…”
Section: Neutrophils and Ochratoxinmentioning
confidence: 99%